A Damage Model of Ultra High Performance Concrete and its Application in Seismic Design of Gravity Dam. Issue 3 (February 2019) - Ma, Tianxiao; Zhang, Liaojun; Xie, Wei; Wang, Weiqiang
Abstract: The ultra high performance concrete is currently the most innovative cement-based engineering material, which has shown a much better performance in strength and durability than the conventional concrete and has received increasing attention worldwide as its application emerges in the engineering field. Based on the theory of damage mechanics, a plastic damage model of the ultra high performance concrete material is established and studied on in this paper. Through the finite element numerical calculation, the rationality of the parameter setting and the applicability of the damage model are verified by comparing its results with those of the cubic compression test and the simply supported beam bending test and then the ultra high performance concrete is introduced to the hydraulic engineering design in this paper. Taking the Koyna gravity dam as an example, a scheme for seismic reinforcement using ultra high performance concrete in the weak part of the gravity dam, which is vulnerable to damage, is proposed. The results show that the scheme can significantly reduce the damage degree of the dam under earthquake action, limit the development of the crack to the upstream and avoid the occurrence of penetrating cracks, as a result of which the seismic performance of the dam is greatly improved. The research results of this paper provide a new idea for high dam design in strong earthquake areas.